Transformation Through Problem Based Learning (PBL) to Improve Team Skills and Managerial Proficiency of Shipping Electrical Cadets Course in Diploma III Study Program - Eddi,; Dwi Santoso, Agus; Harianto, Bambang Bagus (Technium Social Sciences Journal, 2023)
This study aims to determine the influence of the Problem Based Learning (PBL) method in learning Leadership of Teamwork Skills and Managerial Skills on the learning outcomes of Diploma III Electrical Sailing Cadets. This research was conducted at the Surabaya Shipping Polytechnic. The study runs from March to September 2023. The research method used was quasi-experimental with pretest-posttest control group design and sampling techniques with cluster sampling. Class DIV TRPK A as the control class and class DIV TRPK B as the experimental class. The instruments used are test instruments in the form of multiple-choice questions and non-test instruments in the form of student activity observation sheets. Based on the analysis of test data, it was found that there was an influence of the Problem Based Learning (PBL) model on student learning outcomes in learning Leadership of Teamwork Skills and Managerial Skills. It is based on the results.